Eksplorasi Potensi Alami Waduk Menuju Rancangan Wisata Desa Purwosekar Tajinan Kabupaten Malang - Nurin Fitriana fitriana; Eny Dyah Yuniwati; Azhar Adi Darmawan; Rizalnur Firdaus (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The maximum empowerment of village potential is one way to improve the economy. Purwosekar Village, Tajinan Subdistrict, Malang Regency, has the potential of natural and human resources that can be developed. Ownership of a reservoir that was previously neglected, a lot of garbage, sediment, and wild plants will be a very valuable asset if conceptualized water tourism. Moreover, the village community has many skills and handmade products, which are still confused about the marketing media. Thus it is necessary to plan and conceptualize steps to empower the reservoir to become a tourist site which will later be a means of promoting processed products for villagers. The activities carried out are aimed at 1) providing design designs using the SketchUp Pro 3D Design Program for tourism reservoir concepts 2). Provide stages of activities to develop the potential of village tourism village design. This community service activity has an output target in the form of a tourism reservoir design. So that through this service activities can help disseminate the promotion of products created by the village community